An unusual thrombosis of an ostial left internal mammary artery graft causing acute coronary syndrome five years after coronary bypass surgery - Murat Akçay; Ömer Gedikli; Korhan Soylu (KARE Publishing, 2019)
For long-term patency, a left internal mammary artery (LIMA) graft is considered the gold standard for left anterior descending artery (LAD) revascularization. Subsequent occlusion of a LIMA graft may be related to atherosclerosis, narrowing at anastomotic locations, fixed torsions within the graft, straight tubular stenosis, dissection, or vasospasm. Late thrombotic occlusion of a LIMA, however, is rare, and the cause is not known, though case reports can be found in the literature. The present case is a description of the successful revascularization via percutaneous intervention of an ostial LIMA thrombotic occlusion occurring 5 years after bypass surgery in a 71-year old patient diagnosed with acute coronary syndrome.